A Sampling of Perceptions of Potential Users of the Australian Athlete Career and Education Programs - Gorely, Trish; Lavalee, David; Bruce, David; Teale, Brook; Lavalee, Ruth M. (My University, 2001)
This study evaluated the content, quality, access, and delivery of the Australian Athlete Career and Education (ACE) Program. The ACE Program is coordinated by the Australian Institute of Sport (AIS) to provide eligible athletes with skills, resources, and contacts needed to pursue educational goals and/or careers outside of their sport. This objective is met by offering services to eligible athletes, including Olympic-level athletes, scholarship holders, and those in development squads at the AIS and state institutes and academies. Employing both qualitativeand quantitativemethodologies, levels of usage of the program, overall satisfaction with the services provided, and athletes' suggestions for the future were assessed. A two-phase iterative research design was followed to meet the objectives of this study. Phase one was qualitativein nature, and involved six focus group interviews (n=4-8 per interview) with key sub-groups of athletes, and one focus group interview with coaches and administrators (n=5). Then, 867 athletes completed a survey. The final instrument was five pages long and consisted primarily of closed questions focusing on such topics as where athletes find information about the services provided by the ACE Program, how often they accessed ACE services, how satisfied they were with the services they accessed, and what factors led them to (or limited them from) accessing the ACE services. Some open-ended questions (e.g., "If relevant, think of an ACE service that you found satisfactory and state what made the service satisfactory for you") were also included to allow the athletes to expand on issues of satisfaction and future improvements in the service. Results revealed that more than 70% of eligible athletes utilized the programs services within a 12-month timeline, and that the most used services were career planning, educational guidance, and selected professional development courses. Transition services were used by less than one percent of the athletes. Reasons for using the ACE Program were also found to relate to enhancing the athletes' lives both inside and outside of sport. Overall, the athletes were found to be satisfied with the quality of the services provided by the program. Specific targeting of programs based on age and sport was recommended.
Keywords: Australia; student development; transitions; satisfaction